Political spots - Shields, Mark (New Jersey : Time-Life Video, 1982)
The video offers a humorous primer to the techniques used by today's political media makers. Samples spots from across the country, representing all political parties and many levels of goverment. Also introduces media consultants Bob Squire and Bob Goodman
Keywords: Advertising, Political -- United States; Advertising, Political